2009
DOI: 10.1111/j.1440-1819.2009.01980.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of epileptic seizure in substance‐abusing subjects

Abstract: Life-time prevalence of epileptic seizures was assessed in 626 consecutive patients treated for substance abuse. Seizures were reported in 8.63% (9.2% in alcohol abusers, 12.5% in opioid abusers). A total of 64.8% of the seizures were associated with substance use. These occurred during withdrawal in the alcohol cohort and during intoxication with dextropropoxyphene and withdrawal from heroin or poppy husk in the opioid cohort. Results indicate that seizures may be more common in older patients with longer dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 15 publications
1
20
1
Order By: Relevance
“…13,15,16,20 In the present study 26% of the participants were students or unemployed, similar to the findings of other studies. 7,11,12,16,17 Student or unemployed people are more curious to use the substance and easily get influenced by peer groups. In various studies it was observed that students have opportunity of movement from one place to another and they receive monetary assistance from family for educational purpose.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…13,15,16,20 In the present study 26% of the participants were students or unemployed, similar to the findings of other studies. 7,11,12,16,17 Student or unemployed people are more curious to use the substance and easily get influenced by peer groups. In various studies it was observed that students have opportunity of movement from one place to another and they receive monetary assistance from family for educational purpose.…”
Section: Discussionsupporting
confidence: 91%
“…The findings are comparable to findings of other studies. [9][10][11][12][13][14][15][16][17][18] In the present study, majority (62.40%) of the participants were single (unmarried/separated/divorced). This finding was similar with other studies conducted around the different part of the country.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, abuse of prescription pain relievers by pregnant women can result in a number of problems in newborns, referred to as neonatal abstinence syndrome (NAS). This diagnosis has increased by almost 300 percent in the United States between 2000and 2009(CDC, 2013, largely driven by the high rate of opioid prescriptions provided to pregnant women. In the United States, an estimated 14.4 percent of pregnant women are prescribed an opioid during their pregnancy (Bateman et al, 2014).…”
Section: Introduction: Opiate/opioid Epidemic In Americamentioning
confidence: 99%
“…When these substances attach to their receptors, they reduce the perception of pain and can also produce a sense of well-being. On the other hand, they can also produce drowsiness, mental confusion, nausea, and constipation (Mattoo, 2009). The effects of opioids are typically mediated by specific subtypes of opioid receptors (i.e., mu, delta, and kappa), which are activated by the body's own (endogenous) opioid chemicals (i.e., endorphins, enkephalins).…”
Section: Introduction: Opiate/opioid Epidemic In Americamentioning
confidence: 99%